Dissolution of kraft lignin using Protic Ionic Liquids and characterization - Rashid, T. (Elsevier B.V., 2016)
In the present research three Protic Ionic Liquids (pyridinium formate, pyridinium acetate and pyridinium propionate) were synthesized and tested for the dissolution and subsequent regeneration of kraft lignin. Among the investigated solvents, pyridinium formate showed a higher dissolution capacity (70 w/w) i.e. (710 g/L) at 75 Â°C within 1 h. The results indicated that the introduced solvent is thermally stable, noncorrosive, possesses low viscosity and is easy to recycle. The dissolution process is purely physical and the physicochemical analysis of the regenerated lignin showed high thermal stability, with reduction in polydispersity and the average molecular weight was reduced from 4119 g/mol to 1249 g/mol. FTIR spectroscopy and 1H NMR results proved that the regenerated lignin is less degraded. Moreover the OH vibrations of regenerated lignin showed a weak inter and intramolecular interaction in regenerated lignin, which could positively help in reducing its chemical resistance towards processing for further commercial applications. Due to the higher solubility of lignin and its stability towards recyclability, the pyridinium formate proved that present selective dissolution and regeneration of lignin could significantly enhance the pretreatment techniques for lignocellulosic biomass. Â© 2016 Elsevier B.V.